2023
DOI: 10.3390/genes14030717
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Spectrum of the ABCA12 Gene and Genotype–Phenotype Correlation in a Cohort of 64 Patients with Autosomal Recessive Congenital Ichthyosis

Abstract: Autosomal recessive congenital ichthyosis (ARCI) is a non-syndromic congenital disorder of cornification characterized by abnormal scaling of the skin. The three major phenotypes are lamellar ichthyosis, congenital ichthyosiform erythroderma, and harlequin ichthyosis. ARCI is caused by biallelic mutations in ABCA12, ALOX12B, ALOXE3, CERS3, CYP4F22, NIPAL4, PNPLA1, SDR9C7, SULT2B1, and TGM1. The most severe form of ARCI, harlequin ichthyosis, is caused by mutations in ABCA12. Mutations in this gene can also lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The authors speculated that the detected mutations c.4412A>G, p.(His1471Arg) and c.4601C>T, p.(Thr1534Met) do not completely abolish ABCA12 activity, which could lead to an intermediate phenotype resembling EKVP. However, both mutations have already been described in two patients with ARCI in Hotz et al [ 20 ]: the mutation c.4412A>G was detected compound heterozygous with a second pathogenic variant in patient P34; the variant c.4601C>T was found in a homozygous state in patient P5 in this publication. Neither patient showed any features of EKV.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…The authors speculated that the detected mutations c.4412A>G, p.(His1471Arg) and c.4601C>T, p.(Thr1534Met) do not completely abolish ABCA12 activity, which could lead to an intermediate phenotype resembling EKVP. However, both mutations have already been described in two patients with ARCI in Hotz et al [ 20 ]: the mutation c.4412A>G was detected compound heterozygous with a second pathogenic variant in patient P34; the variant c.4601C>T was found in a homozygous state in patient P5 in this publication. Neither patient showed any features of EKV.…”
Section: Discussionmentioning
confidence: 50%
“…Molecular genetic analysis revealed two heterozygous mutations in ABCA12 (transcript ENST00000272895.7, NCBI reference sequence NM_173076.2, GRCh37.p13), including the splice-site mutation c.6962+1G>A, p.?. The mutation on the other allele, c.4139A>G, p.(Asn1380Ser), is the most frequent mutation in ABCA12 [ 20 ]. Her brother, P2, was similar affected since birth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenotypic overlap occurs sometimes. It has been shown that ABCA12 variants correlate with phenotypic severity (Akiyama, 2010 ; Hotz et al., 2023 ; Loo et al., 2018 ; Montalvan‐Suarez et al., 2019 ; Umemoto et al., 2011 ). Current studies generally support that most biallelic truncation variants and/or exon/amino acid deletions lead to HI.…”
Section: Discussionmentioning
confidence: 99%
“…These phenotypic differences occur depending on the type of ABCA12 mutation. Truncating variants on both alleles of ABCA12 tend to lead to HI, and the combination of two missense variants mainly leads to CIE or LI 12,13 . Thus, there are genotype–phenotype correlations.…”
Section: Introductionmentioning
confidence: 99%